The novel microRNA hsa-miR-CHA1 regulates cell proliferation and apoptosis in human lung cancer by targeting XIAP. (June 2019) - Yoo, Jung Ki; Lee, Ji Min; Kang, Seung Hee; Jeon, Seong Ho; Kim, Chang Min; Oh, Seung-Hun; Kim, Chang-Hyun; Kim, Nam Keun; Kim, Jin Kyeoung
Highlights: We identified and characterized novel miRNA (miR-CHA1) in human lung cancer cell. The miR-CHA1 downregulated lung cancer cells and tissues compared with normal cell and tissues. The miR-CHA1 is suppressed cell proliferation and apoptosis in vitro and in vivo by targeting XIAP. These results suggest that miR-CHA1 seem to be apply novel diagnosis and therapeutic target for lung cancer. Abstract: Objectives: MicroRNAs have critical roles in cancer development by regulating the expression of oncogenes or tumor suppressor genes. We identified and characterized a novel miRNA, miR-CHA1, in human lung cancer cells. The aim of this study was to investigate its novel function in human lung cancer by targeting XIAP. Material and methods: Novel miRNA cloning, Real-time qRT-PCR, western blotting, dual luciferase assay, miRNA transfection, proliferation and apoptosis assay were carried on human lung cancer cell line A549. Fifteen paired NSCLC tissues and noncancerous lung tissues were collected. In vivo xenograft assay was performed. Results: Expression of miR-CHA1 was downregulated in human lung cancer cell lines and tissues compared with normal cells and tissues. We identified a putative target gene, XIAP, whose expression was regulated by miR-CHA1 overexpression. XIAP is an inhibitor of apoptosis that represses the activation of caspase 3 and 9. XIAP mRNA and protein levels were directly suppressed by miR-CHA1. XIAP has an important role in carcinogenesis, and previous studies suggest that it may regulate cell survival and proliferation by its anti-apoptotic ability. Conclusion: Taken together, miR-CHA1 inhibited cell proliferation and induced apoptosis in vitro and in vivo by targeting XIAP. These data can be applied to identify novel therapeutic targets for lung cancer therapy.